Life history and reproductive traits of the East Atlantic deep-sea quill worm Hyalinoecia robusta Southward, 1977 (Annelida: Onuphidae). (5th June 2022) - Arias, Andrés; Paxton, Hannelore
Abstract: Polychaetes or bristle worms (Annelida) are one of the best represented invertebrate groups in marine environments worldwide. Although the reproductive biology and life histories of polychaetes from many marine and estuarine habitats are well documented, our knowledge of the reproduction and life cycles of deep-sea polychaetes is still far from comprehensive. Hyalinoeciinae, a subfamily of Onuphidae, one of the most dominant and successful tubicolous deep-sea polychaete families, are characterised by their peculiar lifestyle as free-living epibenthic species, as they protrude from their tubes in a caterpillar-like fashion known as epibenthic crawling. The reproductive biology, sexual strategies and developmental modes of Hyalinoecia spp. are largely unknown. We have studied quarterly samples of the East Atlantic deep-sea quill worm Hyalinoecia robusta Southward, 1977, collected during 2012–2013, from the adjacent slope of the Avilés submarine Canyons System (Bay of Biscay) at 1500 m depth. Here we report on the annual cycle, revealing that H. robusta is iteroparous, reproducing annually during a breeding season from early spring to summer. The performed histological study revealed that the species is a simultaneous hermaphrodite with a previous adolescent male phase. This is the first evidence of the occurrence of hermaphroditism in the subfamily Hyalinoeciinae. Mature sperm was of the ent-aquasperm type and was stored in modified nephridial chambers that develop into external papillae that may detach from the worm and act as spermatophores at the time of reproduction. In H. robusta, the egg fertilisation seems to occur within intersegmental dorsal openings of the worm body wall or inside the worm tube. This hypothesis is consistent with the finding of fertilised eggs and developing embryos attached to the body wall and/or inside the worm tube in some specimens. The herein reported H. robusta reproductive traits do not support their conspecificity with populations from outside North Atlantic Ocean. Thus, the name H. robusta may be hiding other deep-water Hyalinoecia species. Highlights: Hyalinoecia robusta is a simultaneous hermaphrodite with a previous adolescent male phase. Hyalinoecia robusta has ent-aquasperm stored in modified chambers that develop into external papillae acting as spermatophores. Hyalinoecia robusta is parasitised by gregarine protozoans: a newly reported symbiotic association. Reproductive traits of H. robusta do not support their conspecificity with populations from outside N Atlantic. The name H. robusta may be hiding other deep-water Hyalinoecia spp.